Mindfulness in Action: Buddhist Environmental Activism of Earth Holder Berlin - Zhang, Hanyi (Religions, 2024)
This study explores the intersection of mindfulness practice and environmental activism within the Earth Holder Berlin (EHB) group, a part of the Order of Interbeing (O of I) inspired by Thich Nhat Hanh. EHB, established in 2020, integrates the principles of engaged Buddhism and endeavors to advance social and ecological justice through mindful actions. Using a qualitative methodology, this research employs semi-structured interviews and participant observation to investigate the experiences of EHB members. The findings demonstrate the transformative potential of Buddhism in ecological discourse, illustrating how EHB members embody epistemic entanglement, intertwining their Buddhist backgrounds with climate knowledge. This integration not only enhances personal transformation but also serves as a catalyst for social and ecological justice, enriching our understanding of engaged Buddhism in contemporary environmental movements.